The year of the hangman - Blackwood, Gary L. (New York : Dutton Children's Books, 2002)
In 1777, having been kidnapped and taken forcibly from England to the American colonies, fifteen-year-old Creighton becomes part of developments in the political unrest there that may spell defeat for the patriots and change the course of history.
820
Accelerated Reader AR
Keywords: Historical fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Fiction